Hepatic lipid metabolism in adult rats using early weaning models: sex-related differences. (10th October 2020) - Bertasso, Iala Milene; Pietrobon, Carla Bruna; da Silva, Beatriz Souza; Miranda, Rosiane Aparecida; Bonfleur, Maria Lucia; Balbo, Sandra Lucinei; Manhães, Alex Christian; Oliveira, Elaine; de Moura, Egberto Gaspar; Lisboa, Patricia Cristina
Abstract: Non-pharmacological early weaning (NPEW) induces liver damage in male progeny at adulthood; however, pharmacological early weaning (PEW) does not cause this dysfunction. To elucidate this difference in liver dysfunction between these two models and determine the phenotype of female offspring, de novo lipogenesis, β-oxidation, very low-density lipoprotein (VLDL) export, and gluconeogenesis in both sexes were investigated in the adult Wistar rats that were weaned after a normal period of lactation (control group) or early weaned either by restriction of access to the dams' teats (NPEW group) or by reduction of dams' milk production with bromocriptine (PEW group). The offspring received standard diet from weaning to euthanasia (PN180). NPEW males had higher plasma triglycerides and TyG index, liver triglycerides, and cholesterol by de novo lipogenesis, which leads to intracellular lipids accumulation. As expected, hepatic morphology was preserved in PEW males, but they showed increased liver triglycerides. The only molecular difference between PEW and NPEW males was in acetyl-CoA carboxylase-1 (ACC-1) and stearoyl-CoA desaturase-1 (SCD-1), which were lower in PEW animals. Both early weaning (EW) females had no changes in liver cholesterol and triglyceride contents, and the hepatic cytoarchitecture was preserved. The expression of microsomal triglyceride transfer protein was increased in both the female EW groups, which could constitute a protective factor. The changes in hepatic lipid metabolism in EW offspring were less marked in females. EW impacted in the hepatic cytoarchitecture only in NPEW males, which showed higher ACC-1 and SCD-1 when compared to the PEW group. As these enzymes are lipogenic, it could explain a worsened liver function in NPEW males.